Agenesia dental en pacientes jóvenes - A. Bastidas, Mónica; M. Rodríguez, Adriana (Revista Estomatología, 2004)
Dental Ageneses or dental congenital absence is a syndrome seen in world diverse populations and generates a lot of consequences that could be avoided if its diagnosis were opportune done. To determine its prevalence among young bet-ween 14 to 21 years old users of four private or public health services providers located at Santiago de Cali city, a descriptive study was carried out by 1.440 dental stories and its co-rrespondent panoramic x-ray revision in order to determine the number and ratio of dental age-neses present on the age groups. It was found that 141 patients (10 %) had been diagnosed at least one ageneses tooth. On this information basis a clinical examination was accorded whit each patient in order to de-termine relationships among some variables as young gender, age, dental group affected, type of tooth involved, quadrant an arches and, in addition if there were some kind of syndrome that could be related. Special attention was placed on a possible association among third molar and other teeth agenesis.